Over the ivy walls : the educational mobility of low-income Chicanos - Gandara, Patricia C. (SUNY series, social context of education., 1995)
Unique among literature on minority and Chicano academic achievement, Over the Ivy Walls focuses on factors that create academic successes rather than examining school failure. It weaves existing research on academic achievement into an analysis of the lives of 50 low income Chicanos for whom schooling "worked" and became an important vehicle for social mobility. Gandara examines their early home lives, school experiences, and peer relations in search of clues to what "went right."